Development of PBL-Based Worksheets with the Alef Education Platform to Improve Mathematical Reasoning and Independent Learning Skills in Islamic Junior High School Students - A. L. Sirait, Nurhasana; Amin Fauzi, KMS Muhammad; Hasratuddin, Hasratuddin (Jurnal Perspektif, 2025)
The purpose of this study was to determine the validity, practicality, and effectiveness of student worksheets (LKPD) based on PBL assisted by the Alef Education platform, improving students' mathematical reasoning skills, and improving students' learning independence. The type of research used is research and development, the development model used is the Thiagarajan, Semmel learning model, namely the 4-D model. The study was conducted in class VII MTsN Toba Samosir, the research sample was 30 students. The results of the study showed that the LKPD developed was declared valid, practical and effective, the increase in reasoning skills and learning independence of students who learned using LKPD developed with the PBL model assisted by the Alef Education Platform seen from the n-gain was stated to have increased. For this reason, PBL using LKPD assisted by the Alef Education platform can be an alternative for learning mathematics for class VII students.